Comparative analysis of the clinical and epidemiological characteristics of human influenza virus versus human respiratory syncytial virus versus human metapneumovirus infection in nine provinces of China during 2009−2021. Issue 12 (29th August 2022) - Cui, Aili; Xie, Zhibo; Xu, Jing; Hu, Kongxin; Zhu, Runan; Li, Zhong; Li, Yan; Sun, Liwei; Xiang, Xingyu; Xu, Baoping; Zhang, Rongbo; Gao, Zhenguo; et al.
Abstract: A comparative analysis of confirmed cases of human influenza virus (HIFV), human respiratory syncytial virus (HRSV), and human metapneumovirus (HMPV) was conducted to describe their clinical and epidemiological characteristics. During 2009−2021, active surveillance of acute respiratory infections (ARIs) was performed in nine provinces of China. Clinical and epidemiological information and laboratory testing results of HIFV, HRSV, and HMPV were analyzed. Among 11591 ARI patients, the single‐infection rates of HIFV, HRSV, and HMPV were 15.00%, 9.59%, and 2.24%, respectively; the coinfection rate of these three viruses was 0.64%. HIFV infection was mainly in adults aged 15−59 years, accounting for 39.10%. HRSV and HMPV infections were mainly in children under 5 years old, accounting for 87.13% and 83.46%, respectively. Patients with HRSV infection were younger than HMPV. HRSV and HMPV had high similarities in clinical manifestations, presenting with lower respiratory symptoms. HIFV mainly presented with an upper respiratory infection. The epidemic peak of HRSV was earlier than that of HIFV, and that of HMPV was later than those of HRSV and HFIV. A total of 85.14% of coinfection cases were children under 5 years old. Coinfection might increase the risk of pneumonia in HIFV cases. During 2020−2021, the positive rates and seasonal patterns of these three viruses changed due to the impact of the COVID‐19 pandemic. Certain clinical and epidemiological features were observed in HIFV, HRSV, and HMPV infections, which could be beneficial for guiding clinical diagnosis, treatment, and prevention of these three viruses in China.